ANALISIS KEPUTUSAN PEMBELIAN KONSUMEN TERHADAP PRODUK MIE INSTAN (STUDI KASUS PADA MAHASISWA/I STIE RIAU PEKANBARU) - Sundari, Rina (Eko dan Bisnis: Riau Economic and Business Review, 2017)
Today most of the people of Indonesia are familiar with instant food called Instant Noodles. Various brands and variations of taste was already introduced by many instant noodle food manufacturers, this resulted in consumers have a variety of alternative choices in determining the instant noodle products that will be consumed. Population in this research is student / I STIE Riau with amount of sample counted 47 people with technique of stratified random sampling. This research method using descriptive qualitative